Mottainai in Civil Engineering - A Message from Japan - Vaverková, Magdalena Daria; Matsui, Yasuhiro; Vaverka, Igor (Szkoła Główna Gospodarstwa Wiejskiego w Warszawie, 2023)
This article examines the impact of Japan's mottainai concept on civil engineering practices, focusing on the waste of materials, financial resources, and harmonisation of structures with the environment. The authors highlight the global challenges of environmental and social imbalances in the context of global warming. The Japanese concept of mottainai is presented as the key to shaping the civil engineering approach. The inefficient use of raw materials was analysed in terms of material waste. A transition to a closed-loop economy is recommended, emphasising the need for resource efficiency. In the context of financial resources, the need for efficient budget allocation and project management is emphasised. The section on harmonising structures with the environment focuses on aesthetics, environment, sustainable mobility, and an integrated approach to urban planning. Civil engineering projects should combine functional efficiency with respect to the environment, and the mottainai concept can be a tool for achieving sustainability in civil engineering. Innovative solutions, such as intelligent energy management systems, are recommended to improve construction efficiency.
Keywords: civil engineering; material wastage; sustainability; construction; closed-loop economy